Variable-Density Flow and Solute Transport in Stratified Salt Marshes - Xiaojing Wu; Yuansheng Wang; Chengji Shen; Zhongwei Zhao (Frontiers in Marine Science, 2022)
Subsurface hydrodynamics underpin the eco-functions of salt marshes. Many studies have investigated these processes under various conditions. However, the impact of soil stratification (a low-permeability mud layer overlying a high-permeability sand layer) on the variable-density groundwater flow (particularly unstable flow) and solute transport in regularly tide-flooded marshes remains poorly understood. The present study numerically explored this question based on a 2D cross-creek section of salt marshes, by comparing cases with and without stratification. Results show that, the low-permeability mud layer delays the initiation of unstable flow and leads to smaller and denser salt fingers. Consequently, solute plume stays in the marsh soil for a longer time and spreads more widely than that in the homogeneous case. Also, soil stratigraphy extends the duration and shrinks the zone of solute discharge across the tidal creek. Sensitivity analysis was conducted based on three key controlling variables: hydraulic conductivity contrast between mud layer and sand layer ( K mud / K sand ), salinity contrast between surface water and groundwater ( C sea / C pore ), and mud layer thickness ( D mud ). The results demonstrate that the residence time of solute plume in a two-layered salt marsh is less sensitive to C sea / C pore than to K mud / K sand and D mud . Moreover, the commencement and duration of solute discharge are more sensitive to K mud / K sand and D mud than to C sea / C pore . While the location of solute discharge zone is highly sensitive to D mud and slightly influenced by K mud / K sand and C sea / C pore . Findings from this study would facilitate a deeper understanding of the eco-functions of salt marshes.